Jigsaw Cooperative Learning Model for Enhancing Student Interest and Learning Outcomes in Islamic Cultural History - Ratna Kasni Yunindel; Abdul Basit; Muhammad Zalnur; Besral Besral; Resva Ingriza (Fitrah: Journal of Islamic Education, 2026)
Learning outcomes in the Islamic Cultural History course at MIN 6 Padang indicate suboptimal achievement, which is influenced, among other factors, by students’ low interest in the subject. This study aims to analyze the effectiveness of the Jigsaw cooperative learning model in enhancing students’ interest and learning outcomes. The study employed a quasi-experimental approach by comparing learning outcomes before and after the implementation of the Jigsaw model. Data were analyzed using t-tests and ANOVA to test the significance of differences in learning outcomes. The results showed that the post-test significance value was 0.000 (p < 0.05), indicating a significant difference following the implementation of the Jigsaw model. The ANOVA test also yielded a significance value of 0.000, reinforcing these findings. Furthermore, the calculated t-value of 2.580 was greater than the critical t-value of 2.179, indicating that the Jigsaw model had a significant effect on improving learning outcomes. These findings confirm that the Jigsaw cooperative learning model is effective in enhancing students’ interest and learning outcomes in the subject of Islamic Cultural History at the Madrasah Ibtidaiyah.